PROBLEMS OF ASSESSING EDUCATIONAL ACHIEVEMENTS OF HIGHER EDUCATION ACQUIRES DURING DISTANCE EDUCATION OF MATHEMATICAL DISCIPLINES - Repeta , Lesia; Kudzinovska , Inna; Repeta , Viktor (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article examines problems related to the assessment of educational achievements of higher education applicants, the organization of methods of control and testing in distance education mode.